ANALISIS HUKUM PRINSIP ULTRA PETITA OLEH MAHKAMAH KONSTITUSI SEBAGAI UPAYA MEWUJUDKAN KEADILAN SUBSTANTIF DI INDONESIA: MURLINUS - Murlinus (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2022)
This research has two purposes, the first one to explain an untruth principle condition of non ultra petita that is done by Constitutio Court, the second one is to explain a substantive justice concept as a principle of Constitution Court in doing ultra petita compared by principle of non ultra petita according UU. No. 8 2011. Thereby, the reseacht us library reseacht, data analysis result is delivered descriptively, describing, explaining the problems these have relevances with this reseacht clearly and detailed. Data analysis technic that is used is qualitative datas, namely by analyzing seconder datas that found suitable with decided problems frames. The reseacht result indicates that things which gave any reasons in thinking constrction of Constitution Court Judge in giving decisive ultra petita. The judge of Constitution Court thought that essentials or the heart of law to be asked to be judicial review had not been suitable of UUD 1945, until any other sections that connected is stated to be unvalid or not be used. The Constitution Court has a function as quardian of constitution, even if it needs in decision may be happened untruth of procedural of justice prinsiple, in order to be substantive justice. The character of Constitution Court Decision is public or general for everybody. Petitum that appeared in in every aplication said to “judge decides the matter or case must be justifiable”, as a principle for making dicision to be a character of ultra petita for qetting justice.